EVALUASI PETA PERCEPATAN GEMPA SUMATERA (SNI-1726-2002) TERHADAP PETA PERCEPATAN GEMPA MENGGUNAKAN SOFTWARE PSHA - Fahmi Aldiamar (Pusbindiklat - LIPI, 2009)
Evaluation on seismic hazard map in Sumatra bedrock was needed because the Indonesian seismic hazard map standard (SNI-1726-2002) was built using the 2D seismic source model and a lot of seismic activity around Sumatera occurred after the 8N1-1 7 26-2002 was published. Probabilistic Seismic Hazard (PSHA) software was developed by USGS in 2007 to gain bedrock acceleration value derivedf rom Probabilistic calculation on 3D seismic source using the Next Generation Attenuation (NGA). Therefore this software represented the newest theory to build seismic hazard map and it was used in this research to evaluate and validate the Indonesian standard, particularly Sumatra seismic hazard map. Several phases were done to gain the seismic hazard map, such as collecting and processing earthquake data, calculating seismic risk parameter, acceleration calculation using PSHA software and developing a seismic hazard map using ArcGis Software. Evaluation result indicated that SNI-1726-2002 seismic hazard map in Sumatera bedrock, particularly in region 3,4 and 5 was lower than seismic hazard map developed using PSHA software. The deviation was range between ± 0.05-0.20g.